Distinct Regulatory Changes Underlying Differential Expression of TEOSINTE BRANCHED1-CYCLOIDEA-PROLIFERATING CELL FACTOR Genes Associated with Petal Variations in Zygomorphic Flowers of Petrocosmea spp. of the Family Gesneriaceae. Issue 3 (8th September 2015) - Yang, Xia; Zhao, Xiao-Ge; Li, Chao-Qun; Liu, Jing; Qiu, Zhi-Jing; Dong, Yang; Wang, Yin-Zheng
Abstract : Complex and distinct regulatory changes contribute to expression differentiation of CYC- and CIN-like TCP genes and morphological divergence of petals in zygomorphic flowers of Petrocosmea spp. Abstract: CYCLOIDEA ( CYC )-like genes, belonging to the plant-specific TCP transcription factor family that is named after TEOSINTE BRANCHED1 (TB1) from maize ( Zea mays ), CYC from Antirrhinum majus, and the PROLIFERATING CELL FACTORS (PCF) from rice ( Oryza sativa ), have conserved dorsal identity function in patterning floral zygomorphy mainly through specific expression in dorsal petals of a flower. Their expression changes are usually related to morphological diversity of zygomorphic flowers. However, it is still a challenge to elucidate the molecular mechanism underlying their expression differentiation. It is also unknown whether CINCINNATA ( CIN )-like TCP genes, locally controlling cell growth and proliferation, are involved in the evolution of floral zygomorphy. To address these questions, we selected two closely related species, i.e. Petrocosmea glabristoma and Petrocosmea sinensis, with distinct petal morphology to conduct expression, hybridization, mutant, and allele-specific expression analyses. The results show that the size change of the dorsal petals between the two species is mainly mediated by the expression differentiation of CYC1C and CYC1D, while the shape variation of all petals is related to the expression change of CIN1 . In reciprocal F1 hybrids, the expression of CYC1C, CYC1D, and CIN1 conforms to an additive inheritance mode, consistent with the petal phenotypes of hybrids. Through allele-specific expression analyses, we find that the expression differentiation of these TCP genes is underlain by distinctly different types of regulatory changes. We suggest that highly redundant paralogs with identical expression patterns and interspecific expression differentiation may be controlled by remarkably different regulatory pathways because natural selection may favor different regulatory modifications rather than coding sequence changes of key developmental genes in generating morphological diversity.